2013
DOI: 10.5812/ircmj.10180
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vessel Sealing Systems with Conventional

Abstract: BackgroundHaemorrhoids are cushions of submucosal vascular tissue located in the anal canal starting just distal to the dentate line. Haemorrhoidal disease is a common anorectal disorder which has symptoms of bleeding, prolapse, pain, thrombosis, mucus discharge, and pruritus. Haemorrhoidectomy is one of most frequently performed anorectal operation worldwide.ObjectivesThe aim of this study was to compare the effectiveness of the LigaSure tissue sealing device, Harmonic Scalpel and conventional MM open haemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…In fact, thermal damage to tissue seems to be the reason for increased postoperative pain and delay in wound healing. 15,16 In this study we investigated 2 of the most common newgeneration scalpels in head and neck surgery-that is, EBVS and HS-from the point of view of thermal spread in tissues and the consequent histological injury to nerves. The aim was to suggest a safer utilization of each device and to propose a "safety limit" from nerves, which are crucial structures in ENT surgery and in particular in neck dissection, parotid surgery, and thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, thermal damage to tissue seems to be the reason for increased postoperative pain and delay in wound healing. 15,16 In this study we investigated 2 of the most common newgeneration scalpels in head and neck surgery-that is, EBVS and HS-from the point of view of thermal spread in tissues and the consequent histological injury to nerves. The aim was to suggest a safer utilization of each device and to propose a "safety limit" from nerves, which are crucial structures in ENT surgery and in particular in neck dissection, parotid surgery, and thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Peker et al, (12) in the LigaSure group, operation and return to work times were shorter than in the conventional group, while hospitalization and complication rates were similar. In a meta-analysis by Mastakov et al (11) on 11 studies with 1,046 patients, in patients who underwent LigaSure operations, almost all outcome parameters were better than those of the conventional group except complications.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage enables rapid dissection of hemorrhoids without blood. Comparative studies of LigaSure with conventional methods can be found in the literature (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of hemorrhoidal coagulation have been attempted by several authors such as LigaSure system, Harmonic Scalpel, electrothermal coagulation. Peker et al [24] studied 69 patients randomized to LigaSure, Harmonic Scalpel and conventional hemorrhoidectomy. They observed that the postoperative pain and analgesic requirement was much higher in LigaSure and Harmonic Scalpel group.…”
Section: Discussionmentioning
confidence: 99%